Republic of Croatia : Second Review Under the Stand-By Arrangement, and Requests for Waiver of Performance Criteria and for Modification of a Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses the Republic of Croatia's Second Review Under the Stand-By Arrangement, and Requests for Waiver of Performance Criteria and for Modification of a Performance Criterion. Although there were continuing delays in structural reforms, the main performance criteria for end-2001 were observed. The IMF staff supports waivers for the nonobservance of these performance criteria on the grounds that the nonobservance is likely to be largely temporary in the light of an unchanged privatization program, and that there is no evidence that it caused a crowding out of the private sector.